PERSPECTIVE AS A MEANS OF COMPOSITIONAL EXPRESSIVENESS IN ARTISTIC PHOTOGRAPHY - KHYNEVYCH, R. V.; SKLYARENKO, V. O.; SLITYUK, O. O. (Art and Design, 2023)
The aim: determination of the features of the use of perspective in artistic photography as a means of compositional expressiveness. Analysis of geometric and optical aspects of the visual characteristics of different types of perspective in photographic art. Methodology. A comparative analysis of compositional methods of conveying volume and depth of space in artistic photography is applied. Methods of systematization and generalization were used to determine the specific features of different types of perspective in photo art. Results. The peculiarities of the concept of perspective in photography are considered. The common features of works of painting and photo art in the context of conveying the depth and volume of the depicted space are determined. The analysis of the main types of perspective – linear, tonal, aerial, optical and spherical – was performed, using the example of their use in artistic photography. The influence of the perspective construction of the picture on the visual perception of the image and its content is determined. The role of technical means and their parameters in constructing the perspective of a photographic frame is clarified. Scientific novelty. The main methods of displaying the volume and depth of space in a photo image when using different types of perspective are defined. The geometric and optical regularities of perspective as a pictorial means in art photography are revealed. Practical significance. Information on the use of different types of perspective in artistic photography has been studied and systematized. Recommendations are provided for the selection of geometric and optical parameters of the frame for the transmission of visual information in works of photographic art. The obtained results can be used in the educational process in the preparation of bachelors specializing in photo-video design.